Village of Rewey - Keune, Megan; Janke, James (My University, 2009)
The purpose of this study was to gather opinions regarding issues to be considered in the development of the Village of Rewey's comprehensive plan. This summary is one of three summaries included in the Southwest Wisconsin Regional Planning Commission (SWWRPC) Comprehensive Planning project.
22 p.
Keywords: City planning--Wisconsin--Rewey (Village); Rewey (Wis. : Village)--Surveys; Comprehensive plan report; Village of Rewey comprehensive plan; Iowa County, Wisconsin; Rewey (Wis. : Village); Community planning; Public opinion survey; Southwest Wisconsin Regional Planning Commission Comprehensive Planning project; Village of Rewey, Wisconsin; Public opinion--Wisconsin--Rewey (Village); Land use--Wisconsin--Rewey (Village)